Development of A 6-DOF 3D printed industrial robot for teaching and learning / Adamu Yusuf Abdullahi - Adamu Yusuf , Abdullahi (2019)
The trend in modern manufacturing has led to a paradigm shift from the conventional high method to heavily automated processes. This comes with a high cost for those who want to meet up to the increasing pace of this revolution as the machines and the knowledge to control them is becoming expensive. Two major areas that have contributed in shaping this achievement of the industry 4.0 are additive manufacturing and robotics. With the drop in the prices of 3D printers and availability of off-the-shelf (OTS) electronics components, the industrial experience is brought nearer to those who cannot afford it, especially students who need learn the adequate skill-sets in order to efficiently perform in this fourth industrial revolution. To this end, this project aims at building a low-cost 3D printed robotic arm for teaching and learning purpose. The robotic arm was printed using three different kinds of 3D printers, with two most common materials. The forward and inverse kinematics of the robotic arm were derived from using a well-known and easy to understand method. Finally, the robotic was controlled using the Arduino mega 2560 which sends pulse width modulation (PWM) signals to the motors through a serial connection. A simple pick and place experiment using two different objects was conducted using the robotic arm. Also, the joint accuracies of three major joints were calculated. As an educational tool, it is hoped that students will learn the principles of 3D printing, robot kinematics and some level of control.